Pengaruh Padat Tebar Benur terhadap Pendapatan pada Usaha Budidaya Udang Vaname (Litopenaeus Vannamei) - Rijal, Rijal; Megawati Megawati; Yusri Muhammad Yusuf (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2025)
This study aims to determine the effect of fry stocking density on income in vanamei shrimp (Litopenaeus vannamei) farming at PT Esaputli Prakarsa Utama. The research employs quantitative methods using primary and secondary data gathered through participatory observation. Simple linear regression tests, correlation coefficients, and partial tests (t-tests) were used to answer the research questions and test the hypotheses. The results of the study, as determined by the t-test, revealed that stocking density did not have a significant impact. The t-count value was -0.997, which is smaller than the t-table value of 2.896, and the significant value was 0.348, which is greater than 0.05. The recommendations submitted to determine the effect on income are more directed toward the production process of the shrimp farming business.